One Health and Ethnopharmacology Exploration: Medicinal Plants for Treatment of Rabies in Kualin, East Nusa Tenggara, Indonesia - Muntasir, M.; Dean, Muhajirin; Regaletha, Tadeus Andreas Lada; Nabuasa, Bernadeta Stien Julian; Lenggu, Chatrin Jansye; Oematan, Videl Apsi (Manunggal Halim Jaya, 2025)
Rabies is a zoonotic disease caused by the rabies virus and can be fatal if not treated immediately. In Kualin, East Nusa Tenggara, local people have long used traditional medicinal plants to treat rabies. This research aims to explore the types of medicinal plants used by the Kualin community in treating rabies, as well as find out their properties and how to use them. The research method used is descriptive qualitative through interviews and direct observation. The results of the research show that several plants are often used, including soursop (Annona muricata), turmeric (Curcuma longa), ginger (Zingiber officinale), gotu kola leaves (Centella asiatica), and tobacco (Nicotiana tabacum). This ethnopharmacological knowledge needs to be preserved and developed as part of local wisdom in managing public health. Further research is needed to identify and test the effectiveness of medicinal plants used by the community in treating rabies.